Ziauddin Sardar’s Civilizational Science Paradigm: Reconstructing the Integration of Islam and Contemporary Science - Khoirun Nisa; Nadia Arrifqi; Amanda Putri; Helmi Syaifuddin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This essay is based on a paper titled Reinterpreting Sardar's idea of Civilizational Science as a means of reconciliation between Islam in this world science with Sometimes it is difficult to grasp what Sardar's paradigm means in the philosophy of science and how knowledge can be integrated across various fields in the Muslim the context. Hence, this paper aims to investigate how Sardar views the Islamic values' compatibility with modern scientific knowledge and what the implications of civilizational science on the philosophy of science as well as knowledge integration within the contemporary Muslim world can be social responsibility, human welfare (maṣlaḥah), and justice ('adl). It highlights in particular Sardar's view of science as not just factual accumulation, but as a civilizational task that requires ethically scrutiny on its Besides, the paper points out that his framework is able to handle the uncertainties, complexities, and changes characteristic of Postnormal Times. Finally, through Indonesian examples it explains that Islamic higher education is compatible with the ideals of the dual curriculum system. Civilizational Science is not only a criticism of modernist ideology but also a norm a basis for cultivating an eth i cal human ist ic future- oriented Islamic civilization.